Hubungan Karakteristik Demografi dengan Perilaku Komplain (Studi Di Rumah Sakit Umum Daerah Badung) - Aprillianty, Anak Agung Sagung Mas Evy; Wardana, Made (E-Jurnal Manajemen; Vol 3 No 8 (2014), 2014)
This study aims todetermine the relationship of demographic characteristics with complaint behaviorin Badung Hospital. Respondents in this study is 100 people. Data analysis techniques used in this study is descriptive statistical analysis, chi-square analysis and crosstabs. The results of this study found that only in come that have a significant relationship with complaint behavior. Suggestions for Badung Hospitalis to improve the delivery channel complaints and clarify the procedures and requirement sareused.
Keywords: demographic characteristic; post service failure behavior; complaint behavior